2002
DOI: 10.4141/p01-016
|View full text |Cite
|
Sign up to set email alerts
|

Stand establishment in processing carrots – Effects of various temperature regimes on germination and the role of salicylates in promoting germination at low temperatures

Abstract: Rajasekaran, L. R., Stiles, A. and Caldwell, C. D. 2002. Stand establishment in processing carrots -Effects of various temperature regimes on germination and the role of salicylates in promoting germination at low temperatures. Can J. Plant Sci. 82: 443-450. The effects of various temperature regimes on carrot seed germination and the possibility of hastening germination at a low temperature using salicylates were studied. Seeds were incubated at various temperatures viz., 25, 20, 15, 10, 5 and 2°C. Salicylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 22 publications
4
11
0
1
Order By: Relevance
“…In addition, the germination percentage of seeds under salinity stress was markedly higher with SA application than without, especially at the highest stress level of 200 mM NaCl (Figure 1). These results are consistent with those of Rajasekaran et al (2002) and Shakirova et al (2003) who showed a promotion in seed germination with SA application.…”
Section: Resultssupporting
confidence: 95%
“…In addition, the germination percentage of seeds under salinity stress was markedly higher with SA application than without, especially at the highest stress level of 200 mM NaCl (Figure 1). These results are consistent with those of Rajasekaran et al (2002) and Shakirova et al (2003) who showed a promotion in seed germination with SA application.…”
Section: Resultssupporting
confidence: 95%
“…The exogenous application of SA may influence a range of diverse processes in plants, including seed germination, ion uptake and transport, and membrane permeability. These results are consistent with those of Rajasekaran et al (2002) and Shakirova et al (2003), who showed that seed germination is promoted by the application of SA. Gutierrez-Coronado et al (1998) have also reported a similar increase in the growth of shoot and roots of soybean plants under normal conditions in response to SA treatment.…”
Section: Discussionsupporting
confidence: 95%
“…Further studies proved that not only SA, but also its putative precursors, benzoic acid (BA) and ortho-hydroxy-cinnamic acid (oHCA), and other related compounds such as aspirin or 2,6-dihydroxy BA may have a protective role against chilling stress in young maize plants Horváth et al, 2002). Similarly, not only SA, but other related compounds, such as 2,6-dihydroxy BA or aspirin (acetyl-SA), hastened the germination of carrot seeds at 5°C (Rajasekaran et al, 2002). It should also be mentioned, however, that these compounds, like SA, may cause severe damage to the plants when applied above a certain concentration at normal growth temperature: a significant decrease was detected in the photosynthetic capacity and the growth rate.…”
Section: Exogenous Sa and Related Compounds May Alleviate The Cold-inmentioning
confidence: 99%